PERSPEKTIF GENDER DALAM NOVEL CINTA DI DALAM GELAS KARYA ANDREA HIRATA KAJIAN FEMINISME - Munawaroh, Siti (Jurnal Sastra Aksara, 2019)
The problems discussed in this preparation are about gender perspective in the novel Cinta Di Dalam Gelas by Andrea Hirata. While the purpose of this study was to describe a gender perspective in the novel Cinta Di Dalam Gelas by Andrea Hirata. Hirata uses feminism analysis. In describing the image and the constructing role in this novel, reading and note-taking techniques are used. Reading technique is a technique used to obtain data by reading the entire text. Reading techniques are used to read the novel Cinta Di Dalam Gelas by Andrea Hirata. Note technique is used to record things related to the analysis of feminism in the novel Cinta Di Dalam Gelas by Andrea Hirata. Then outlines the existing data so that it becomes a meaningful meaning. The results of this arrangement are to discuss the image of women based on a gender perspective and the role of women based on a gender perspective which is portrayed in the novel with daily character activities as well as social values ​​which are a real reflection of human life. The image and role in this novel take more from the first players like Maryamah from the main character called Enong a woman who can match men. While the images and roles depicted in this novel are flat, all characters have their own image and role. That is about how to behave correctly, to behave properly. Also the wrong behavior and attitude as learning that the behavior is wrong. Mutual respect is expressed intelligently in this novel. The depiction of the image and role in this novel is to make learning for the community and prospective society. and struggling how to fight for equality with men.